2008
DOI: 10.1136/jmg.2008.057984
|View full text |Cite
|
Sign up to set email alerts
|

Double outlet right ventricle: aetiologies and associations

Abstract: Background: Double outlet right ventricle (DORV), a clinically significant congenital heart defect, occurs in 1-3% of individuals with congenital heart defects. In contrast to other major congenital heart defects, there are no systematic or comprehensive data regarding associations, aetiologies, and pathogenesis of DORV. We analysed reported cases in the medical literature to address these issues. Methods: We queried the PubMed database using key words ''double outlet right ventricle'' and ''DORV'' for case re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 187 publications
1
80
1
1
Order By: Relevance
“…Apoptosis can play a crucial role in the alignment of the arteries (20). Of note, although increased apoptosis was noted in the myocardium or the mesenchyme in the Mox2-Cre DKOs, this did not occur in the Tie2-Cre model at e13.5.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Apoptosis can play a crucial role in the alignment of the arteries (20). Of note, although increased apoptosis was noted in the myocardium or the mesenchyme in the Mox2-Cre DKOs, this did not occur in the Tie2-Cre model at e13.5.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, the DKOs exhibited DORV, in which both great arteries (the pulmonary artery and the aorta) originate from the right ventricle. DORV is a clinically important congenital heart defect resulting from various cellular events, including proliferation and migration defects of neural crest cells, delayed or increased apoptosis in the myocardium of the conotruncal area, and faulty left/right signaling (20). We have been able to narrow down the defective cell types that likely underlie the DKO DORV phenotype to the endothelial cells and/or the mesenchymal cells of the pulmonary and aortic valves/atrioventricular canal, where the Tie2-Cre is known to be expressed (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Knock-out of various genes in mice has resulted in DORV (reviewed in Ref. 50), suggesting that DORV represents a final common pathway defect during cardiac outflow tract development. These mouse models point to the involvement of at least several signaling pathways in this aspect of heart development, including the Ras/extracellular signal-regulated kinase (Erk), transforming growth factor ␤, Wnt, Notch, retinoic acid, and others (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…These mouse models point to the involvement of at least several signaling pathways in this aspect of heart development, including the Ras/extracellular signal-regulated kinase (Erk), transforming growth factor ␤, Wnt, Notch, retinoic acid, and others (reviewed in Ref. 50).…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that trisomies 13 and 18 and deletion 22q11 increase the risk of DORV (13), although our patient refused to undergo chromosomal studies. Owing to the diversity of DORV, several distinct pathogenetic mechanisms for DORV have been postulated, including impairment of neural crest derivative migration and impairment of normal cardiac situs and looping (13). An error during neural crest development can also cause cervicocephalic artery anomalies.…”
Section: A B Cmentioning
confidence: 99%